Effects of a universal prevention program on externalizing behaviors: Exploring the generalizability of findings across school and home settings. (December 2019) - Muratori, Pietro; Bertacchi, Iacopo; Masi, Gabriele; Milone, Annarita; Nocentini, Annalaura; Powell, Nicole P.; Lochman, John E.; Jones, Shannon; Kassing, Francesca; Romero, Devon
Abstract: Universal prevention approaches have significantly reduced children's conduct problems and aggressive behavior in the school setting, but it has not been clear whether the effects generalize into children's behavior in home and community settings in later elementary school years. The present study examined this issue using a classroom-randomized design, with 1030 students in 70 fourth and fifth grade Italian classes. The intervention model is the Coping Power Universal and the classroom teachers delivered it. Coping Power Universal produced a significant reduction in both parents' and teachers' rated conduct problems, relative to control classes, indicating that universal prevention can produce significant reductions in children's conduct problems that generalize into the home and community settings. The intervention also increased children's prosocial behaviors in school and home settings. The Coping Power Universal is a short intervention model that is believed to be a useful strategy for children's behavioral problems in the broad population.